2014
DOI: 10.1016/j.jtcvs.2013.03.023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative nutritional status on postoperative outcomes in children undergoing surgery for congenital heart defects in San Francisco (UCSF) and Guatemala City (UNICAR)

Abstract: Objective To determine the association between preoperative nutritional status and postoperative outcomes in children undergoing surgery for congenital heart defects (CHD). Methods Seventy-one patients with CHD were enrolled in a prospective, two-center cohort study. We adjusted for baseline risk differences using a standardized risk adjustment score for surgery for CHD. We assigned a World Health Organization Z-score for each subjects’ preoperative triceps skinfold measurement, an assessment of total body f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
3
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 33 publications
2
98
3
13
Order By: Relevance
“…14 According to the study, a lower total body fat mass, as well as acute and chronic malnourishment were associated with worse clinical outcome, assessed by the length of ICU stay, duration of mechanical ventilations, and duration of dopamine and milrinone infusion. 14 The other characteristics of our cohort were that malnourished patients were of younger age, presented more often with acyanotic heart defects at the time of congenital heart surgery, and had higher PRISM III score. A previous study reported that heart failure, older age at corrective surgery and lower growth potential (lower birth weight, small for gestation, lower parental anthropometry and associated genetic syndrome) emerged as significant predictors of malnutrition at the presentation of the patients.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…14 According to the study, a lower total body fat mass, as well as acute and chronic malnourishment were associated with worse clinical outcome, assessed by the length of ICU stay, duration of mechanical ventilations, and duration of dopamine and milrinone infusion. 14 The other characteristics of our cohort were that malnourished patients were of younger age, presented more often with acyanotic heart defects at the time of congenital heart surgery, and had higher PRISM III score. A previous study reported that heart failure, older age at corrective surgery and lower growth potential (lower birth weight, small for gestation, lower parental anthropometry and associated genetic syndrome) emerged as significant predictors of malnutrition at the presentation of the patients.…”
Section: Discussionmentioning
confidence: 86%
“…On average, our malnourished patients tended to be extubated 12 hours after those counterpart patients with normal nutritional status; this is consistently reported in many different sets of patients. 5,[12][13][14] In comparison to our study, a study 14 investigated the influence of the nutritional status based on skinfold thickness, instead of weight for age. 14 According to the study, a lower total body fat mass, as well as acute and chronic malnourishment were associated with worse clinical outcome, assessed by the length of ICU stay, duration of mechanical ventilations, and duration of dopamine and milrinone infusion.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, patients with a higher blood albumin level showed lower BNP values and lower inotrope use during their hospital stay. [34][35][36] Children with chronic diseases and an increased inflammatory cytokine level have growth hormone resistance, so nutritional status and cytokine levels are the main determinants of such resistance. Proinflammatory cytokines, such as TNF-α, act on the CNS by altering appetite and energy metabolism and provide a signal that causes the loss of muscle mass (nuclear factor kB and ATP-dependent ubiquitin proteolytic pathways).…”
Section: A) Nutritional Carementioning
confidence: 99%
“…Además, los pacientes con mayor albuminemia mostraron menores valores de PNC y menor uso de inotrópicos durante su hospitalización. [34][35][36] Los niños con enfermedades crónicas y con aumento de citoquinas inflamatorias presentan resistencia a la hormona del crecimiento, por lo que el estado nutricional y los niveles de citoquinas son los principales determinantes de esta resistencia. Las citoquinas proinflamatorias, como TNF-a, actúan en el SNC alterando el apetito y el metabolismo energético, y proporcionan una señal que causa la pérdida de masa muscular (factor nuclear kB y vías proteolíticas ubiquitina dependientes de ATP).…”
Section: A) Cuidados Nutricionalesunclassified